2012
DOI: 10.1055/s-0032-1315209
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Triterpenoid Saponins from the Roots of Ilex asprella

Abstract: Two new sulfur-containing triterpenoid saponins, asprellanosides A (1) and B (2), were isolated from the roots of Ilex asprella, together with 10 known compounds (3-12). An in vitro anti-HSV-1 activity test of the isolates (1-4, 6-7, and 9-12) showed that only asprellanoside A (1) and oblonganoside H (6) exhibited anti-HSV-1 activity with TIC values of 0.14 and 0.18 mM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The HMBC spectrum (Table 1, Figure 3) showed correlation peaks between the H-1 0 ( H 4.68) of arabinose and C-3 ( C 106.4) of the aglycone, as well as the H-1 00 ( H 6.37) of glucose and C-28 ( C 95.8) of the aglycone, affirming that the glycosidation positions of b-arabinose and b-glucose are located on C-3 and C-28 of the triterpenoid sapogenin, respectively. These data were similar to those of asprellanoside A (Zhou et al 2012). However, the formula weight of 1 was 80 Da greater than that of asprellanoside A, which can be ascribed to a SO 3 H group.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The HMBC spectrum (Table 1, Figure 3) showed correlation peaks between the H-1 0 ( H 4.68) of arabinose and C-3 ( C 106.4) of the aglycone, as well as the H-1 00 ( H 6.37) of glucose and C-28 ( C 95.8) of the aglycone, affirming that the glycosidation positions of b-arabinose and b-glucose are located on C-3 and C-28 of the triterpenoid sapogenin, respectively. These data were similar to those of asprellanoside A (Zhou et al 2012). However, the formula weight of 1 was 80 Da greater than that of asprellanoside A, which can be ascribed to a SO 3 H group.…”
Section: Resultssupporting
confidence: 79%
“…According to a previous report, only two triterpenoids from the roots exhibited anti-HSV-1 activity (Zhou et al 2012). Our results demonstrate that both compound 1 and 2 have antiviral activity against the H1N1 influenza virus in A549 cells.…”
Section: Discussionmentioning
confidence: 87%
“…From a literature review in pharmacological reports of IA, we found that many researches are focused on its hydroalcoholic extract, only Zhou et al reported that triterpenoid saponins from IA have anti-HSV-1 activity (Zhou et al, 2012). We hypothesize that total saponins may be the active ingredients in antiinfluenza virus.…”
Section: Discussionmentioning
confidence: 81%
“…Triterpenoid glycosides have been reported to possess various biological activities, including anti‐inflammatory, antitumor promoter, antiviral, and cytotoxic activities. [] Naturally occurring triterpenoid glycosides usually have an O ‐bond between the aglycone (triterpenoids) and sugar moieties. Recently, N ‐glycosides were synthesized from steroids and reported to have cytotoxicity against human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%